Functionalization of fluorinated ionic liquids: A combined experimental-theoretical study - Ferreira, Margarida L. (2022)
FCT/MCTES (Portugal), through: grant SFRH/BD/130965/2017 (M.LF.); Investigador FCT 2014 (IF/00190/2014 to A.B.P. and IF/00210/2014 to J.M.M.A.); projects PTDC/EQU-EQU/29737/2017, PTDC/QEQ-FTT/3289/2014 and IF/00210/2014/CP1244/CT0003. Associate Laboratory for Green Chemistry-LAQV, financed by national funds from FCT/MCTES (UID/QUI/50006/2019). projects 2018-LC-01 and 2019-URL-IR1rQ-011, from Obra Social "la Caixa" and by Khalifa University through project RCII-2018-0024.